Śląsk Cieszyński w refleksjach humanistów – poszukiwanie klucza do zrozumienia narracji o przygranicznym mikroświecie - Bortliczek, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
Searching for metaphors that allow us to understand the linguistic picture of Cieszyn Silesia and their residents, I refer to the anthology of conversations experienced by people with authority. The conversations influence the change and development of Cieszyn’s microcommunity and borderland (microworld). I analyse the language (common words, terms, names, and especially metaphors). The work includes three parts: the picture of space in metaphors, man in the space of Cieszyn Silesia (truths and myths) and names and brand names in the local microworld. I reach the conclusion that the metaphors describing the local community, one the one hand, grow it on tradition, culture and history and, on the other hand, express the current observations, for example about Cieszyn Silesia and its esotericism. The phenomenon of esotericism serves people’s judgment (as it is stated by some interlocutors) and sustains the opposition: autochthons are from here while strangers are not. The architectural icons of Cieszyn Silesia (for example Rotunda, Piast’s Tower) coexist with, e.g. the local taste (for example, Cieszyn cookies). Out of concern for Cieszyn Silesia identity, the knowledge about the borderland microworld should consciously be passed on from generation to generation.